Evaluation of quality of life in patients with muscular dystrophy by sociodemographic characteristics (Annals of Medical Research, 2022)
Aim: Genetic myopathies are diseases that progress and impair quality of life. It was aimed to evaluate the relationship between socio-demographic characteristics and the quality of life of 146 patients.Materials and Methods: The WHOQOL-BREF scale was applied, and the scores in the questionnaire were converted to WHOQOL 4-20 and WHOQOL 0-100 score ranges and the relationships between the WHOQOL-BREF questionnaire results were evaluated.Results: There was no significant difference in the scale results according to gender and age (p>0.05 for all). There were significant findings regarding education level, marital status, and disease severity on the WHOQOL-BREF scale.Conclusion: It is thought that it can be a reference for researchers by revealing the findings that will increase the patient's quality of life.
Keywords: Myopathy; Muscular dystrophy; Quality of life; WHOQOL-BREF; Rehabilitation